Development of A Website-Based Library Information System at LKIA Pontianak School - Nikolaus Deskon; Ade Restu Juliansyah; Muhammad Ihsan Kamil; Gabriel Arsenius Sandria Umbing; Yulio Andre Rian Kristian Nitbani (PT. PENERBIT TIGA MUTIARA, 2024)
This research intends to develop a website-based library information system that is expected to increase the reading interest of Sekoah residents and also make it easier for library staff to work more effectively so that it can improve the literacy skills of LKIA Pontianak school residents. This research is a type of Research and Development or Research and Development (R&D). The purpose of this Research and Development is to produce media in the form of a website. The product developed is then tested for feasibility by validating and testing the website product. The design of the development of a website-based library information system at LKIA Pontianak school uses the ADDIE development model. Validation is carried out to determine the feasibility of the library website before it is implemented in the implementation of digital libraries. The validation was carried out by a validator consisting of one system and media expert at the LKIA Pontianak school.The result of the research is the development of a library information system made in the form of a website to make it easier for librarians and students to find books such as package books, fiction books and nonfiction books. With this library information system, students can borrow books, be it fiction books, nonfiction books and package books. Where currently LKIA Pontianak School does not have a website-based school library information system. For this reason, LKIA Pontianak School needs to implement the School Library Information System.